A ternary hybrid CdS/SiO2/TiO2 photoanode with enhanced photoelectrochemical activity. (November 2018) - Li, Lin; Chen, Rong; Zhu, Xun; Liao, Qiang; Ye, Dingding; Zhang, Biao; He, Xuefeng; Jiao, Long; Feng, Hao; Zhang, Wei
Abstract: In this study, a novel ternary hybrid CdS/SiO2 /TiO2 film was proposed as the phonoanode for the photocatalytic fuel cell. The samples were characterized by X-ray diffraction, scanning electron microscopy and UV–vis absorption. The photoelectrochemical activity of the ternary hybrid electrode was characterized by the photocurrent-time transient response, linear sweep voltammetry and electrochemical impedance spectroscopy. It was shown that CdS/SiO2 /TiO2 yielded much higher photoelectrochemical activity than CdS/TiO2 and bare TiO2 did. The photoanode with CdS/SiO2 /TiO2 showed the highest photocurrent density of 4.6 mA cm −2, exhibiting a 40% improvement over the conventional CdS/TiO2 photoanode. The roles of SiO2 and CdS in such a ternary configuration were elaborated. It was demonstrated that CdS could act as an excellent visible light captaturer to generate photo-induced charge carriers, and SiO2 as a passivation layer to suppress the interfacial recombination of electrons and holes. Moreover, SiO2 could allow for more CdS to be deposited at the photoanode owing to its high adsorption capacity. In addition, the effects of the SiO2 content and the SILAR cycle time on the performance of the CdS/SiO2 /TiO2 photoanode were investigated. An optimal SiO2 content of 10% could yield the best performance. Increasing the SILAR cycle time could improve the photoelectrochemical activity. Highlights: A novel ternary hybrid CdS/SiO2 /TiO2 photoanode is proposed. The developed photoanode yields the enhanced photoelectrochemical. The roles of SiO2 and CdS in the ternary configuration are elaborated.